On the Function of Late Acheulean Stone Tools: New Data From Three Specific Archaeological Contexts at the Lower Palaeolithic Site of Revadim, Israel. (2nd October 2018) - Zupancich, Andrea; Solodenko, Natalya; Rosenberg-Yefet, Tamar; Barkai, Ran
ABSTRACT: The Acheulean represents one of the most widespread cultural complexes spanning from Africa to Eurasia between 1.8 and 0.2 Mya. The site of Revadim, located on the southern coastal plain of Israel, represent one of the rare opportunities allowing to perform detailed functional analysis of stone tool assemblages from such old contexts. This paper presents data originating from the functional analysis of three lithic assemblages coming from two areas of the site (B and C). Our results suggest that at Revadim most of the tools were used for the processing of soft materials, possibly related to butchering activities along with some tools used to process vegetal materials and bone. The evidence here presented highlight the use wear potentials of Revadim and its implication in the investigation of the range of activities performed by Levantine Acheulean early human groups.